Peran Komunikasi Kepemimpinan Camat Dalam Membangun Motivasi Kerja Pegawai Kecamatan Lembah Gumanti Kabupaten Solok - Deni Fitria (CV. ITTC INDONESIA, 2026)
This study aims to determine the role of the Sub-district Head's leadership communication in building employee work motivation at the Lembah Gumanti Sub-district Office, Solok Regency. The research background is based on the importance of a leader's communication style in creating a conducive work climate, increasing morale, and encouraging the effectiveness of sub-district apparatus performance. The research method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results indicate that the Sub-district Head's leadership communication has a significant influence on employee work motivation. Open, persuasive, and participatory communication can increase employee responsibility, loyalty, and discipline. However, several obstacles were also identified, such as differences in perception, limited communication time, and organizational culture factors that influence the effectiveness of message delivery. This study concludes that effective leadership communication plays a crucial role in building employee work motivation. Therefore, it is recommended that the Sub-district continue to strengthen communication patterns that are more intensive, transparent, and adaptive to employee needs.